ASAL MUASAL KEMATIAN MANUSIA DAN TRADISI KUMPUL KELUARGA DALAM BUDAYA CINA - Zhang Wei (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This article explores the relationship between the myth ‘Chang’e Flying to the Moon’ and the subject of family reunion at Mid-autumn festival. An analysis based on Claude Levi-Strauss’ structuralist theory reveals that the fairy tale is concerned with the origin of human death in order to teach descents of a family to be good to family members as one cannot become alive again when he/she is claimed by death.